2014
DOI: 10.1523/jneurosci.2352-13.2014
|View full text |Cite
|
Sign up to set email alerts
|

Medial Septum-Diagonal Band of Broca (MSDB) GABAergic Regulation of Hippocampal Acetylcholine Efflux Is Dependent on Cognitive Demands

Abstract: The septohippocampal pathway contains cholinergic, GABAergic, and glutamatergic projections and has an established role in learning, memory, and hippocampal theta rhythm. Both GABAergic and cholinergic neurons in the medial septum-diagonal band of Broca (MSDB) have been associated with spatial memory, but the relationship between the two neuronal populations is not fully understood. The present study investigated the effect of selective GABAergic MSDB lesions on hippocampal acetylcholine (ACh) efflux and spati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
50
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 71 publications
(53 citation statements)
references
References 80 publications
3
50
0
Order By: Relevance
“…Cholinergic neuron activity is, thus, necessary for the transition from inactive to active hippocampal-related behavior, but is inefficient in inducing significant change in the activity of the hippocampal neurons during arousal states (Mamad et al 2015). Moreover, optogenetic activation of septal cholinergic neurons increases hippocampal activity within the theta band (2-6 Hz) in anesthetized mice (Vandecasteele et al 2014), and exploratory tasks have been reported to increase AchC in hipoccampus (Roland et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Cholinergic neuron activity is, thus, necessary for the transition from inactive to active hippocampal-related behavior, but is inefficient in inducing significant change in the activity of the hippocampal neurons during arousal states (Mamad et al 2015). Moreover, optogenetic activation of septal cholinergic neurons increases hippocampal activity within the theta band (2-6 Hz) in anesthetized mice (Vandecasteele et al 2014), and exploratory tasks have been reported to increase AchC in hipoccampus (Roland et al 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Cholinergic signaling from the MS and DB to the hippocampus is certainly important for formation of spatial memories: ACh has consistently been shown by microdialysis to be elevated in the hippocampus during performance of various memory tasks (Mitsushima et al, 2013; Roland et al, 2014; Stanley et al, 2012), and numerous studies have probed the effects of exogenous – and more recently endogenous - ACh on hippocampal plasticity and performance in spatial memory tasks (Cobb and Davies, 2005; Kutlu and Gould, 2016). Blockade of mAChR signaling locally in the hippocampus impairs memory (Carli et al, 1997; Wallenstein and Vago, 2001).…”
Section: Cholinergic Signaling and Circuits Involved In Attentionmentioning
confidence: 99%
“…Spatial memory is akin to episodic memory, and strictly depends on the hippocampus for consolidation and retrieval (Moscovitch et al, 2005). Moreover, hippocampus-dependent spatial and discriminative learning and memory also involve the basal forebrain (Roland et al, 2014), a prominent source of cholinergic input to the medial temporal lobe (Damasio et al, 1985). This includes the areas containing the medial septal-diagonal band of Broca involved in temporal associations and the nucleus basalis for sustained attention (Mesulam et al, 1983;Olton et al, 1988).…”
Section: Explicit Memorymentioning
confidence: 99%